HYDRO CHEMICAL CHARACTERIZATION OF GROUNDWATER AND LOGON OF OUALIDIA AREA, MOROCCO - Jghalef, Boubker; Alwashali, Ebrahim; Ashraf, Chakir; Abdelhak, Guemimi (European Scientific Journal, ESJ, 2014)
Our work aims to study the physical-chemical water quality of the lagoon of Oualidia and surrounding wells used in agriculture to assess the impact of saline water on the hydrochemical groundwater quality. This is part of a program to safeguard the lagoon of Oualidia. We conducted a companion water extraction on several wells in the agricultural field near the lagoon and governed by the National Office for Agricultural Development Doukkala (ORMVAD). To each well, we specify the GPS location and the groundwater level. We thus classified the wells, according to their geographical locations into three groups: "DOUAR BAKIR ", "DOUAR OULAD LHLAL " and "Other collection". The majority of wells has a hydrochemical facies chlorinated and sulfated calcium and magnesium included all groundwater " DOUAR OULAD LHLAL " upstream, with the exception of groundwater " DOUAR BAKRI " in the center who has a facies hyper chlorinated lime, hyper sulfated calcium, indicating a slight intrusion of the marine water table that this caused a change in the nature of these hydrochemical groundwater waters. However, this issue is clearly pronounce the novel water source flowing into the lagoon faces which completely turned in chlorinated sodium and potassium intake by sodium chloride and lagoons that have substituted the sulfate ions, calcium and magnesium. The analysis of main components includes wells on its chemical characterization. Water lagoon and wells near of it have a strong mineralization which shows the interchange between the lagoon and the wells by the issue of infiltration